Synthesis of Novel N4-Hydrocytidine Analogs as Potential Anti-SARS-CoV-2 Agents - Franck Amblard; Julia C. LeCher; Ramyani De; Shu Ling Goh; Chengwei Li; Mahesh Kasthuri; Nicolas Biteau; Longhu Zhou; Zahira Tber; Jessica Downs-Bowen; Keivan Zandi; Raymond F. Schinazi (MDPI AG, 2022)
Coronavirus disease 2019 (COVID-19) is an emerging global pandemic with severe morbidity and mortality caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Molnupiravir, an ester prodrug form of N4-hydroxycytidine (NHC), was recently emergency-use approved for the treatment of early SARS-CoV-2 infections. Herein, we report the synthesis and evaluation of a series of novel NHC analogs.